Electrochemical magneto-immunoassay for detection of zika virus antibody in human serum - Castro, Karla R.; Setti, Grazielle O. [UNESP]; de Oliveira, Tássia R.; Rodrigues-Jesus, Mônica J.; Botosso, Viviane F.; Perini de Araujo, Ana P.; Durigon, Edson L.; Ferreira, Luis C.S.; Faria, Ronaldo C. (Elsevier, 2023)
Zika virus (ZIKV) is a flavivirus transmitted by infected Aedes genus mosquitoes. An infected person may be asymptomatic or present symptoms such as fever, arthralgia, and in pregnancy it may lead to neurological disorders in the fetus, such as microcephaly. Based on the high dissemination potential of ZIVK and its similar antigen composition to other arboviruses, new approaches for selective virus detection are urgently needed. This work reports the development of an electrochemical immunoassay for detection of anti-ZIKV antibodies, using magnetic beads functionalized with recombinant protein derived from the non-structural protein 1 (ΔNS1-ZIKV) and anti-IgG antibodies labeled with horseradish peroxidase (HRP) enzyme. The magneto-immunoassay uses disposable microfluidic devices for detection of anti-ZIKV in serum samples. A linear response was obtained for a wide concentration range from 0.01 to 9.80 × 105 pg mL−1 (r2 = 0.982), with a limit of detection of 0.48 pg mL−1. The proposed immunoassay proved to be highly efficient for the detection of anti-ZIKV antibodies in serum, offering promising perspectives for the development of fast, simple, and affordable point-of-care diagnosis devices for ZIKV.
Keywords: Disposable microfluidic device; Electrochemical immunoassay; Magnetic beads; Zika virus infection